Educational Leadership Development and the Implementation of Innovative Schooling Practices - Margaret C. Wang; Richard M. Englert; JoAnn B. Manning (Educational Considerations, 1989)
Instructional leadership development has been identified as a primary goal of training programs of many of the OERI-funded LEAD centers. (Program Approaches to Administrative Training and Development.)